PENGEMBANGAN MEDIA PEMBELAJARAN SENI SEBAGAI MEDIA DAKWAH DIKALANGAN MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR - Darmawan, Gilang; Rohimah, Rt Bai; Miftahudin, Miftahudin; Saepudin, Saepudin; Imamudin, Imamudin; Tabrani, M. Bayi (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
The essence of Islamic da'wah is an invitation or call to the way of Allah Subhaanahu wa ta'aalaa (SWT), for goodness and truth according to the teachings of the Qur'an. The purpose of this article is to find out how art is a medium for da'wah and to know the role of art in preaching. The benefits of this article scientifically are that it can enrich scientific treasures and add information about art as a medium of da'wah. Then the practical benefits are as a reference and motivation for Muslims in general, for readers and writers in particular to always continue to carry out da'wah to spread Islamic law. Art is a beautifully nuanced expression. Whether it's speech or expression, painting or verbal, in short in all aspects of life. With science everything becomes easier, with art everything becomes more beautiful. Da'wah media is a tool used to convey da'wah material (Islamic teachings) to mad'u (recipients of da'wah).